Green Synthesis of Silver Nanoparticles as a Wound Healing Agent: a Systematic Review of the Biological Activities - Galih Priambodo; Widiastuti Samekto; Agus Subagio; Hardhono Susanto; Luky Dwiantoro (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The implication of nanotechnology includes silver nanoparticles to medical sciences, and has a revolutionary impact on therapeutic and diagnostics management. Many studies reported that silver nanoparticle (AgNPs) application can accelerate the wound healing process. This study aimed to systematically review the biological activities of silver nanoparticles as a wound-healing agent.Subjects and Method: This article was a systematic review study conducted by searching for articles from online databases such as EBSCO, PubMed, Science Direct, and World Scientific. Populations: laboratory animals; Intervention: green synthesis of silver nanoparticles; Comparison: a standard ointment for wounds such as povidone-iodine, etc; Outcome: wound healing. The independent variable is the green synthesis of silver nanoparticles, and the dependent variable is wound healing. The inclusion criteria for this study were full articles using an experimental study, with the publication year until 2022. The data extraction was focused on the biological activities of silver nanoparticles and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations for systematic reviews.Results: A total of 8 articles reviewed in this study were from countries: Egypt, India, Saudi Arabia, Singapore, and China. The green synthesis of AgNPs was accomplished using a natural aqueous extract from leaves such as Azadirachta indica, Tridax procumbens, the combinations of Catharanthus roseus and Azadirachta indica, Scutellaria barbata, the fungus Fusarium verticillioides, or cyanobacterial platforms (ex: Phormidium sp., Synechocystis sp, and arthrospira sp polysaccharides). All studies were animal-based experimental with wounds infected with bacteria and inflicted in regards to the experiment. All trials resulted in favor of the AgNPs ointment treated group compared to the untreated group or the standard ointment group.Conclusion: Our review suggested that all studies about the efficacy of AgNPs as wound-healing therapy showed positive results.Keywords: biological activities, silver nanoparticles, wound healing.Correspondence: Galih Priambodo. Faculty of Medicine, Universitas Diponegoro. Jl. Prof. Sudarto, Tembalang, Kec. Tembalang, Kota Semarang, Central Java. Email: g2_37@yahoo.co.id. Mobile: 085229998999.Indonesian Journal of Medicine (2023), 08(01): 100-113https://doi.org/10.26911/theijmed.2023.08.01.10